Integrated market and nonmarket strategies: Political campaign contributions around merger and acquisition events in the energy sector - Holburn, Guy L. F.; Vanden Bergh, Richard G. (Strategic Management Journal, 2014)
We examine how firms use political strategies to protect economic rents created by mergers and acquisitions against dissipation by regulators. In regulated industries, regulators can impose costly merger conditions, for instance consumer rate reductions in the utilities sector, thereby reducing shareholder gains. We investigate empirically whether and how firms use election campaign contributions to politicians as a method of influencing regulatory merger approvals. In a statistical analysis of campaign contributions by all electric utilities from 1998 to 2006, we find that utilities increased their contributions in the year before they announced a merger and that merging utilities increased their contributions more in states with greater political party competition. Our findings contribute to political strategy research by providing novel evidence that firms integrate market and nonmarket strategies . Copyright © 2013 John Wiley & Sons, Ltd.